Traumatic Thoracolumbar Spine Fractures: Radiographic Outcome after Transpedicular Screw Fixation (Medical Forum Monthly, 2024)
Objective: To determine the radiographic outcome of transpedicle screw fixation in patients who had sustained traumatic thoracolumbar spine fractures,Study Design: Quasi-experimental study,Place and Duration of study: This study was conducted at the Department of Neurosurgery, Ayub Teaching hospital, Abbottabad from January, 2017 to August, 2017,Materials and Methods: All patients of both genders who had suffered from traumatic thoracolumbar spine fractures and were between the ages of 20 to 60 years were included in the study. All patients underwent detailed history and clinical examination. Spinal fractures were fixed with transpedicular screw fixation using C-arm guidance and under general anesthesia by an experienced neurosurgeon. Pre- and post-operative spinal radiographs of the affected region were taken in both lateral and anteroposterior views to calculate the height of vertebral body, kyphotic angle and sagittal index.Results: Out of sixty patients who were included in this study, mean age of study participants was 39.24±7.24 years. There were 46 male patients and 14 female patients with male to female ratio of 3.28:1. The mean vertebral body height, kyphotic angle and sagittal index were 52.42 mm, 9.77 degrees and 21.9 degrees before surgery respectively while they were 9.30 mm, 3.59 degrees and 5.52 degrees after the surgery respectively. Paired t-test showed that the differences were statistically significant (p-value < 0.001).Conclusion: Transpedicle screw fixation is an effective and reliable way of managing thoracolumbar spine fractures. It not only helps in early restoration of spinal anatomy but also improves functional outcome in these patients. Radiological parameters are helpful in determining the outcome in immediate postoperative period. But, other parameters like clinical and functional must also be taken into account to predict the long term outcome in these patients.